2021
DOI: 10.1002/cam4.3921
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of treatment‐free remission recommendations in chronic phase chronic leukemia patients treated with frontline tyrosine kinase inhibitors

Abstract: Background Tyrosine kinase inhibitors (TKI) can be safely discontinued in chronic phase chronic myeloid leukemia (CP‐CML) patients who had achieved a sustained deep molecular response. Based on the results of discontinuation trials, recommendations regarding patient selection for a treatment‐free remission (TFR) attempt had been proposed. The aims of this study were to evaluate the rate of patients eligible for TKI discontinuation and molecular recurrence‐free survival (MRFS) after stop according to recommenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The National Comprehensive Cancer Network (NCCN) guidelines describe criteria for TKI discontinuation as being the duration of approved TKI therapy for at least 3 years and stable MR4 for ≥ 2 years [ 12 ], which is less strict than the ELN recommendations. Etienne et al published the results of their evaluation of the rate of patients eligible for TKI discontinuation and MRFS after stopping according to several recommendations/guidelines, including the ELN and the NCCN [ 23 ]. They found that the MRFS of patients who fulfilled the selection criteria proposed by the ELN was significantly different from that of those who did not, whereas no difference in MRFS was observed regarding the criteria proposed by the NCCN.…”
Section: Discussionmentioning
confidence: 99%
“…The National Comprehensive Cancer Network (NCCN) guidelines describe criteria for TKI discontinuation as being the duration of approved TKI therapy for at least 3 years and stable MR4 for ≥ 2 years [ 12 ], which is less strict than the ELN recommendations. Etienne et al published the results of their evaluation of the rate of patients eligible for TKI discontinuation and MRFS after stopping according to several recommendations/guidelines, including the ELN and the NCCN [ 23 ]. They found that the MRFS of patients who fulfilled the selection criteria proposed by the ELN was significantly different from that of those who did not, whereas no difference in MRFS was observed regarding the criteria proposed by the NCCN.…”
Section: Discussionmentioning
confidence: 99%
“…48 The Sokal score strongly influences the probability of achieving a sustained DMR rather than the risk of relapse after TKI discontinuation. 52,53 One survey reported that 19% of patients who meet discontinuation criteria are not interested in stopping TKI treatment. 54 In particular, patients with a good quality of life, not experiencing significant side effects from TKI, could be uncomfortable with the interruption of their life-saving therapy.…”
Section: Requirements For Tki Discontinuationmentioning
confidence: 99%
“…Recent guidelines do not include the Sokal risk score, while it is mentioned in the European Society for Medical Oncology (ESMO) guidelines, 50 Australian indications for clinical practice, 51 and the above‐cited MDACC update 48 . The Sokal score strongly influences the probability of achieving a sustained DMR rather than the risk of relapse after TKI discontinuation 52,53 …”
Section: Requirements For Tki Discontinuationmentioning
confidence: 99%
“…There is controversy on how to best use TKIs. Which are the best and most cost-effective strategies to achieve TFR, to optimize survival and improve QoL [ 2 , 7 9 , 35 , 36 , 38 , 41 46 ]? Which strategy(ies) should be used when someone does not meet proposed TKI stopping criteria or fails because of molecular, cytogenetic and/or haematologic leukaemia recurrence?…”
Section: Are Current Recommendations For Tki-therapy Appropriate?mentioning
confidence: 99%
“…Expert consensus statements and clinical practice guidelines recommend >5 years of imatinib and >3 to 5 years of a 2G-TKI, with a response ≥ MR 4 for ≥2 years [ 2 , 7 9 , 38 , 44 , 46 , 48 , 49 ]. Convincing data supporting these recommendations are lacking [ 10 ].…”
Section: How Many People Can Successfully Discontinue Tki Therapy?mentioning
confidence: 99%